Branka Kalenić Ramšak, Jasmina Markič, Barbara Pihler, Maja Šabec: Hispanistična razpotja: Rojas, Cervantes, Machado, García Márquez - Ignac Fock (Ars & Humanitas, 2014)
Ljubljana: Znanstvena založba Filozofske fakultete Univerze v Ljubljani, Zbirka Razprave, 2013, 261 strani